Barriers and Facilitators in Reaching and Supporting Parents with Intellectual Disabilities - Maroesjka Van Nieuwenhuijzen; Sanna Koet; Marcia Lever (Disabilities, 2025)
Support of parents with intellectual disabilities should be long-term and start as early as possible. They, however, often come only into view late. The aim of the present study was to examine the barriers and facilitators in reaching and supporting parents with intellectual disabilities and young children in the Netherlands. Fourteen professionals, three volunteers, and three mothers with intellectual disabilities participated in four focus groups. Results revealed four themes: (1) improve professional development, (2) mutual professional/parent distrust, (3) strengthen support network systems, and (4) improve child welfare system responses. Professionals and policymakers lack knowledge of parents with intellectual disabilities and skills to build trust and support them adequately. Professional development is warranted. The informal network and involvement of fathers is limited and, thus, could be increased. Finally, the way the system is organized impedes adequate support. Long-term involvement and, thus, a different use of resources is needed. Reaching parents with intellectual disabilities as early as possible is important but challenging due to multiple interacting factors. Integral actions at multiple levels are essential to improve preventive care for these parents.